Desain Bahan Pembelajaran Matematika Berbasis M-Learning Berorientasi Pada Kemampuan Berpikir Kreatif Dan Kemandirian Belajar - Nugraha, Guruh (STAI Al-Bahjah, 2023)
Development of Teaching Materials Based on M-Learning on Material Opportunities for Vocational High School Students Oriented to Mathematical Creative Thinking Ability and Learning Independence. This development research refers to the development steps by Allesi & Trollip with procedures that include planning, design and development. The purpose of this development research; (1) Producing M-Learning-based teaching materials on opportunity material for SMK students, (2) Producing M-Learning-based teaching materials that are oriented towards creative thinking skills, (3) Producing M-Learning-based teaching materials that are oriented towards independent learning. Data collection techniques used interview guidelines, material expert questionnaires, media expert questionnaires and student response questionnaires as well as test instruments. Product testing consists of alpha testing and beta testing. This research produces teaching materials based on m-learning in the form of applications on Android smartphones, namely mastery of mathematics. The product developed is considered suitable for use with an average value of material expert validators 4.4, media expert assessment 3.89 with a feasible category and teaching materials are considered oriented to creative thinking skills with an average validation of 4 with a very feasible category, and self-oriented learning with an average validity of 4.43 with a very feasible category.